Moralities: a contemporary discourse between new atheism and Islam - Rehman, Ataur (Penerbit Universiti Kebangsaan Malaysia, 2020)
Atheists deny the existence of God and strongly oppose all religious faiths especially Islam after 9/11. They use scientific, philosophical, historical and moral arguments mainly to prove the non-existence of God. They portray religion as illogical and irrational. Moreover, they argue that religions provide poor guidance on moralities. New atheists suggest that science should replace the religion in order to define what is moral or immoral. On contrary, Muslim scholars defend and argue that religion is main factor behind good moral values. The study focus on the moral dimension of new atheists’ argumentation and the Muslim scholarly response. For this purpose, arguments of four founding fathers of new atheists and four renowned Muslim scholars are comparatively analyzed. New atheists attempt to develop science based moralities and eliminate the role of religion from all important areas of life. Muslim scholars illustrate that position of atheism is illogical and irrational. Moralities are impossible without God and these are outside of scientific domain. Objective moralities need a final authority to decide what is right and what is wrong, atheism lacks this authority.